Identification and Characterization of Marine Debris on Teluk Penyu Beach, Cilacap - Lady Ayu Sri Wijayanti; Gilar Budi Pratama; Andini N.A.; Raziq Aldin; Ismail Maqbul; Mochamad Ramdhan Firdaus (JURNAL PESISIR DAN LAUT TROPIS, 2025)
This study was conducted at Teluk Penyu Beach, Cilacap Regency, with the aim of analyzing the composition, density, and primary sources of marine debris in the area. Sampling was carried out from October to November 2024 using a 5×5 m quadrat transect method along the shoreline, with a 20 m distance between transects. The results showed that a total of 2,021 debris pieces were collected, with the main composition consisting of wood debris (1,485 pieces; 62.80%), plastic (469 pieces; 19%), other materials (294 pieces; 14.58%), plastic foam (42 pieces; 2.60%), fabric (10 pieces; 1.12%), and rubber (7 pieces; 0.17%). The highest debris density was found in the wood category, with 12 pieces/m², followed by plastic (3.752 pieces/m²), plastic foam (0.336 pieces/m²), other materials (0.16 pieces/m²), fabric (0.133 pieces/m²), and rubber (0.14 pieces/m²). Based on the Clean-Coast Index (CCI) calculation, the beach cleanliness index score of 8 indicates that Teluk Penyu Beach falls into the "moderate" category. These findings suggest that the primary source of debris in the area originates from wood waste transported from Segara Anakan through the Nusakambangan Strait, as well as tourism and fishing activities. Sustainable coastal environmental management efforts are necessary to mitigate pollution impacts, including increasing public awareness and implementing ecosystem-based waste management strategies. Keywords: anthropogenic pollutants, Clean-Coast Index, coastal debris, lagoon, wood ABSTRAK Penelitian ini dilakukan di Pantai Teluk Penyu, Kabupaten Cilacap dengan tujuan untuk menganalisis komposisi, kepadatan, dan sumber utama sampah laut di kawasan tersebut. Pengambilan sampel dilakukan pada bulan Oktober–November 2024 menggunakan metode transek kuadrat 5x5 m di sepanjang garis pantai dengan jarak 20 m antar transek. Hasil penelitian menunjukkan bahwa total sampah yang terkumpul sebanyak 2.021 potongan dengan komposisi utama berupa sampah kayu (1.485 potongan; 62,80%), plastik (469 potongan; 19%), bahan lain (294 potongan; 14,58%), busa plastik (42 potongan; 2,60%), kain (10 potongan; 1,12%), dan karet (7 potongan; 0,17%). Kepadatan sampah tertinggi ditemukan pada kategori kayu dengan 12 potongan/m², diikuti plastik (3,752 potongan/m²), busa plastik (0,336 potongan/m²), bahan lain (0,16 potongan/m²), kain (0,133 potongan/m²), dan karet (0,14 potongan/m²). Berdasarkan perhitungan Clean-Coast Index (CCI), nilai indeks kebersihan pantai sebesar 8 menunjukkan bahwa Pantai Teluk Penyu masuk dalam kategori “sedang.” Temuan ini mengindikasikan bahwa sumber utama sampah di kawasan ini berasal dari limbah kayu yang terbawa dari Segara Anakan melalui Selat Nusakambangan, serta aktivitas wisata dan perikanan. Upaya pengelolaan lingkungan pesisir yang berkelanjutan diperlukan untuk mengurangi dampak pencemaran, termasuk melalui peningkatan kesadaran masyarakat dan pengelolaan limbah berbasis ekosistem. Kata kunci: antropogenik polutan, Clean-Coast Indeks, debris pesisir, kayu, laguna